Personnel strategy and their realization at the Belarusian enterprises - Alena, Vankevich (Journal of Business Economics and Management, 2005)
In the article problems of the theory and practice of development of personnel strategy of the enterprises are reflected. The basic kinds of personnel strategy are opened, the forms of their realization, the international experience is investigated. The dialectics of personnel positions of the Belarus enterprises for 1991–2003 is investigated, influence of a labor market on the given processes is shown. Necessity of transition to strategy of socially responsible re‐structuring is proved. Theoretical bases and applied aspects of realization of strategy of socially responsible re‐structuring at the enterprises of Byelorussia are given. First published online: 14 Oct 2010